Hypertension types defined by clinic and ambulatory blood pressure in 14 143 patients referred to hypertension clinics worldwide. Data from the ARTEMIS study. Issue 11 (November 2016) - Omboni, Stefano; Aristizabal, Dagnovar; De la Sierra, Alejandro; Dolan, Eamon; Head, Geoffrey; Kahan, Thomas; Kantola, Ilkka; Kario, Kazuomi; Kawecka-Jaszcz, Kalina; Malan, Leoné; Narkiewicz, Krzysztof; Octavio, José A.; et al.
Abstract : Objective: The Ambulatory blood pressure Registry TEleMonitoring of hypertension and cardiovascular rISk project was designed to set up an international registry including clinic blood pressure (CBP) and ambulatory blood pressure (ABP) measurements in patients attending hypertension clinics in all five continents, aiming to assess different daily life hypertension types. Methods: Cross-sectional ABP, CBP and demographic data, medical history and cardiovascular risk profile were provided from existing databases by hypertension clinics. Hypertension types were evaluated considering CBP (≥140/90 mmHg) and 24-h ABP (≥130/80 mmHg). Results: Overall, 14 143 patients from 27 countries across all five continents were analyzed (Europe 73%, Africa 3%, America 9%, Asia 14% and Australia 2%). Mean age was 57 ± 14 years, men 51%, treated for hypertension 46%, cardiovascular disease 14%, people with diabetes 14%, dyslipidemia 33% and smokers 19%. The prevalence of hypertension was higher by CBP than by ABP monitoring (72 vs. 60%, P < 0.0001). Sustained hypertension (elevated CBP and ABP) was detected in 49% of patients. White-coat hypertension (WCH, elevated CBP with normal ABP) was more common than masked hypertension (elevated ABP with normal CBP) (23 vs. 10%; P < 0.0001). Sustained hypertension was more common in Europe and America and in elderly, men, obese patients with cardiovascular comorbidities. WCH was less common in Australia, America and Africa, and more common in elderly, obese women. Masked hypertension was more common in Asia and in men with diabetes. Smoking was a determinant for sustained hypertension and masked hypertension. Conclusion: Our analysis showed an unbalanced distribution of WCH and masked hypertension patterns among different continents, suggesting an interplay of genetic and environmental factors, and likely also different healthcare administrative and practice patterns. Abstract : Supplemental Digital Content is available in the text